RESEARCH FOR BUILDING INTELLIGENT DIGITAL CONTROL CONTAIN IN VIETNAM AND A MATHEMATICAL FORMULA TO CALCULATE THE CONVEYOR SYSTEM LENGTH - Le Hai Khanh, Nguyen (International Journal of Research -GRANTHAALAYAH, 2024)
This article investigates a novel approach to converting container seaports into digital transformations on old port platforms to maximize land area for production. This model is not only suitable for Vietnam but is also applicable to numerous container seaports worldwide, ranging from small to large, including those considered smart. According to VCCI (2022), digital technology can unlock the potential of seaports. Despite the information provided by VCCI indicating that the port system in Vietnam extends across the country, it has not received adequate investment in IT applications. Royal Haskoning DHV, a leading global technical consulting group in the fields of industry, seaports, maritime, and technical infrastructure, aims to steer Vietnam's seaports, including container seaports, towards a greener and smarter direction. The first step in this transformation is supply chain integration. According to their perspective, improvements in transport links promise to enhance efficiency and reduce congestion in the port area. Scheduled timings for trucks, setting timelines for loading and unloading goods, and the digitization of processes enable managers to interact with the supply chain in real-time. Valdés Figueroa & Pérez (2020) suggests that the future of logistics digitization involves a shift from individual developments to logistics intelligence, in the article titled “Digital transformation in Latin American and Caribbean logistics”. In terms of technology, planning layers, industry guidelines, and the foundation of programs, plans, and projects must be appropriately anchored at higher political levels. This alignment will enable the synchronization of industry rules and regulations with the logistics landscape, promoting the digitization of processes to reduce inefficiencies, cost overruns, and negative externalities. This, in turn, enhances productivity and competitiveness, fostering economic growth and social inclusion among populations both now and in the future. The study introduces a new idea for efficiently incorporating digital technology into the reform of container seaports, making them smarter and stimulating production. This, in turn, contributes to the economic growth of the region and the country as a whole.